A marker placement laser device for improving repeatability in 3D-foot motion analysis - Kalkum, Eva; Drongelen, Stefan van; Mussler, Johannes; Wolf, Sebastian Immanuel; Kuni, Benita (Gait & posture, 2016)
Background - In 3D gait analysis, the repeated positioning of markers is associated with a high error rate, particularly when using a complex foot model with many markers. Therefore, a marker placement laser device was developed that ensures a reliable repositioning of markers. We report the development and reliability of this device for the foot at different tape conditions. - Methods - In 38 subjects, markers were placed at the foot according to the Heidelberg foot measurement method. Subjects were tested barefoot and barefoot with three different tape conditions. For all conditions, a static standing trial was captured. We analyzed differences in distances between markers and the intra-class correlation coefficients (ICC). - Results - Small differences between the conditions (0.03-3.28mm) and excellent ICCs (0.91-0.97mm) were found for all parameters. - Conclusion - The laser marker placement device appeared to be a reliable method to place markers on a tape at previously palpated positions and ensures an exact position. The device could find a wide application in different clinical research fields.
Gesehen am 07.05.2020